Classification of facies of sediments from the reef island Barrang Lompo, Spermonde Archipelago, Indonesia - Yannis Kappelmann; Hildegard Westphal; Dominik Kneer; Henry C Wu; Andre Wizemann; Jamaluddin Jompa; Thomas Mann (PANGAEA, 2023)
The dataset is based on 50 soft carbonate sediment samples from the reef island Barrang Lompo in the Spermonde Archipelago, Sulawesi, SE Asia. The subsurface samples were obtained by percussion drilling at 5 coring locations on the island. From each coring location, 10 samples were retrieved in 1 m intervals, thus providing samples from a maximum depth of 10 m below surface at each site (1 m, 2 m, ..., 10 m). Laboratory data was collected between 2019 and 2021. The provided dataset contains the classification of facies. Percentages of compositions in samples were calculated by adding up relative counts of skeletal components for each samples (i.e. 200 components from fraction >2 mm plus 200 from fraction 2-1 mm plus 100 from fraction 1-0.5 mm). The collected data provides information of reef-derived sedimentation in the Holocene in the Spermonde Archipelago. It provides insight into the ecological background and the origin of the skeletal sediments.
In: Kappelmann, Y et al. (2023): Grain size, skeletal components and C14 measurements of sediments from the reef island Barrang Lompo, Spermonde Archipelago, Indonesia [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.954709